The Role of Specific Nutritional Interventions For The First 1000 Days of Life Program In Stunting Prevention : A Literature Review - Putri, Viorika Marsafa; Yulizawati, Yulizawati; Hardisman, Hardisman; Lipoeto, Nur Indrawaty; Ayunda, Aldina; Lisa, Ulfa Farrah (Asosiasi Pendidikan Kebidanan Indonesia (AIPKIND), 2024)
Background: Stunting has many negative impacts on the health and quality of children so it is necessary to prevent stunting. Prevention of stunting is carried out in accordance with the target of the Sustainable Development Goals, which is to eliminate all forms of malnutrition by 2030 by implementing specific nutrition interventions in the first 1000 days of life program. Purpose: This study aims to determine the role of specific nutritional interventions in the first 1000 days of life in stunting prevention. Methods: This type of research is a narrative literature review. This research was conducted from October 2021 to June 2022. The search for articles was accessed through the Pubmed, Science Direct, and Google Scholar databases. Articles were selected based on inclusion and exclusion criteria. Results: The analysis was carried out on 16 research articles. It was found that every program in specific nutrition interventions can reduce the stunting with prevent stunting by preventing and treating the causes of stunting with the help of the government to create a program so that it can be implemented in more detail and specifically. Conclusion: Specific nutrition has been proven to reduce stunting